“Get Well Enough to Make the Right Decision for Themselves”—Experiences and Perspectives of Clinicians Working with People with Serious Mental Illness and Their Substitute Decision Makers - Samuel Law; Vicky Stergiopoulos; Juveria Zaheer; Arash Nakhost (Behavioral Sciences)
In the current clinical psychiatric practice in most of the world, treatment decisions are based on a person’s capacity to make these decisions. When a person lacks the capacity to understand and appreciate treatment decisions, in many jurisdictions a third-party substitute decision maker (SDM) is appointed on his or her behalf in order to promote safety and optimal clinical outcome. In Ontario, Canada, for example, family members (typically) or public guardians are appointed as SDMs, and they form an integral part of the medical–legal system in psychiatric care. Clinicians working with both patients and their SDMs in these circumstances encounter unique challenges and deliver care in specialized ways, though little research has focused on their experiences and reflections. Based on focus group data, this qualitative study uses a descriptive and interpretative phenomenological approach through thematic analysis to examine these aspects from clinicians working in both inpatient and outpatient settings of an urban teaching hospital’s psychiatric services in Toronto, Canada. Seven key themes emerged: Clinicians (1) appreciate hardships and challenges in lives of SDMs and patients—including the challenging emotions and experiences on both sides, and the risks and relational changes from being an SDM; (2) have an understanding of the patient’s situation and respect for patient autonomy and wishes—they are promoter of autonomy and mindful of patients’ prior wishes amidst patients’ fluctuating capacity, facilitating communication, keeping patients informed and promoting transitioning from SDM to self-determination; (3) have a special working relationship with family SDMs—including supporting SDMs, avoiding harm from delayed or denied treatment, and educating and collaborating with SDMs while maintaining professional boundaries; (4) at times find it difficult working with SDMs—stemming from working with over-involved or uninterested family SDMs, coping with perceived poor SDM decisions, and they sometimes ponder if SDMs are necessary; (5) delineate differences between family and Public Guardian and Trustee (PGT) SDMs—they see PGT as closely aligned with medical decision makers, while family SDMs are more intimately involved and more likely to disagree with a physician’s recommendation; (6) recognize the importance of the SDM role in various contexts—through seeing social values in having SDMs, and acknowledging that having SDMS help them to feel better about their actions as they work to protect the patients; and (7) express ideas on how to improve the current system—at public, societal, and family SDM levels. We conclude that clinicians have unique mediating roles, with privilege and responsibility in understanding the different roles and challenges patients and SDMs face, and have opportunities to improve patient and SDM experiences, clinical outcomes, carry out education, and advocate for ethically just decisions. These clinical roles also come with frustration, discomfort, moral distress and at times vicarious trauma. Clinicians’ unique understanding of this complex and nuanced intersection of patient care provides insight into the core issues of autonomy, duty to care and protect, advocacy, and emotional dynamics involved in this sector as a larger philosophical and social movement to abolish SDMs, as advocated by the Convention on the Rights of Persons with Disability (CRPD), is taking place. We briefly discuss the role of supported decision making as an alternative as.